The Society of Accountants in Edinburgh 1854-1914: A Study of Recruitment to a Profession (Book). - Miranti, Paul J. (The Accounting Review, 1989)
Reviews the book "Society of Accountants in Edinburgh 1854-1914: A Study of Recruitment to a Profession," by Stephen P. Walker.